Factors Influencing Overall Brand Equity And Identification In Local Cultural Heritage Products: A Case Study On Indonesian Millennial And Gen Z Generations - Sifa Azzahra; Iwa Sanjaya; Jeanne Lukman; Jonathan Ermanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to look into the variables affecting overall brand equity and identification in locally produced cultural heritage goods among Indonesian millennials and Gen Z. While overall brand equity serves as a moderator variable, the study focuses on brand awareness, perceived quality, brand associations, brand loyalty, and perceived brand localness (PBL) as independent factors and the dependent variable is intention to purchase. Design/methodology/approach: A sample of 300 respondents from the Jabodetabek neighborhood, Indonesia, were used in a quantitative manner. Questionnaires that were circulated electronically were used to collect data. Regression analysis, factor analysis, and reliability tests were all used to examine the correlations between the different variables. Findings: The data show that brand associations, brand loyalty, and perceived brand localness (PBL) all have a big impact on overall brand equity. Brand equity, however, is not greatly influenced by brand awareness and perceived quality. In addition, overall brand equity significantly influences purchase intention in a favorable way. Research limitations/implications: The study is restricted to a certain geographic area and an age range, which may prevent it from being generalized. Furthermore, the study ignores influences from outside the specified setting and only looks at context-specific characteristics. Originality/value: This study advances our knowledge of how perceptions of brand localness, brand loyalty, and brand associations affect total brand equity in the context of locally produced goods with a rich cultural heritage. Additionally, it emphasizes how important total brand equity is in influencing millennial and Gen Z consumers in Indonesia's purchasing decisions. Keywords: Brand Awareness; Perceived Quality; Brand Association; Brand Loyalty; Brand equity; Perceived Localness; Purchase Intention; Local Fashion Heritage.